Pengembangan Media Boneka Tangan Berbahan Alam Terhadap Perkembangan Bahasa Anak Usia 5-6 Tahun Di TK Negeri PembinaÂ MelatiÂ Tondo - Dian Permatasari Roslina; Andi Agusniatih agusniatih; Amrullah; Nurhayati (Universitas Muhammadiyah Kuningan, 2025)
The purpose of this research and development is to determine the improvement of children's language skills through the use of natural hand puppet learning media. The type of research used is research research in the context of R&D (Reserach and Development). The research and development method (Research and Development) according to (Rustamana et al., 2024:61), is one type of research that is often used in education. By using data collection steps such as observation, interviews, documentation. The results of the recapitulation of observations on children's language skills, from 15 children who were the subjects of the study in three aspects, namely: 1) the aspect of mentioning vocabulary; 2) the aspect of answering questions; 3) the aspect of telling the contents of the story has the same number in each aspect, namely there are no children (0%) in the BSB and BB categories, there are 10 children (67%) in the BSH category, there are 5 children (33%) in the MB category.